2004
DOI: 10.1103/physrevlett.92.173401
|View full text |Cite
|
Sign up to set email alerts
|

Evaporative Cooling of Helium Nanodroplets with Angular Momentum Conservation

Abstract: Evaporative cooling of helium nanodroplets is studied with a statistical rate model that includes, for the first time, angular momentum conservation as a constraint on the accessible droplet states. It is found that while the final temperature of the droplets is almost identical to that previously predicted and later observed, the distribution of total droplet energy and angular momentum states is vastly more excited than a canonical distribution at the same temperature. It is found that the final angular mome… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 13 publications
0
30
0
Order By: Relevance
“…In that case, the deformation of the droplet might result in an anisotropic potential and alignment of the molecule. Later, evaporative cooling of droplets were revisited with a statistical model including the angular momentum conservation, and it was concluded that a significant fraction of the alignment of the total angular momentum should be transferred to the rotational angular momentum of an embedded molecule [29].…”
Section: Discussionmentioning
confidence: 99%
“…In that case, the deformation of the droplet might result in an anisotropic potential and alignment of the molecule. Later, evaporative cooling of droplets were revisited with a statistical model including the angular momentum conservation, and it was concluded that a significant fraction of the alignment of the total angular momentum should be transferred to the rotational angular momentum of an embedded molecule [29].…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown 36 that some of the angular momentum deposited in the droplet during the pick-up process may be kept in the impurity atom, resulting in a different angular momentum distribution from the Boltzmann one. This could yield that some Mg atoms are actually closer to the drop surface.…”
Section: A Thermal Motion and Angular Momentum Effectsmentioning
confidence: 99%
“…If we assume the droplets statistically distribute this energy, the temperature of the droplets will raise to several K, typically above the λ transition of bulk helium. Following this temperature jump, the droplets will rapidly cool by helium evaporation [83,101].…”
Section: Evaporative Cooling and The Temperature Of Helium Nanodropletsmentioning
confidence: 99%
“…However, the evaporative cooling calculations predict that for droplet in the size range studied in most experiments, the spread of final energies for a given droplet size is determined by the evaporation energy, not the energy fluctuations of a canonical ensemble. Perhaps more importantly, an isolated droplet must also conserve total angular momentum, J, and thus should be described by an ensemble that has both E and J as good quantum numbers [101].…”
Section: Evaporative Cooling and The Temperature Of Helium Nanodropletsmentioning
confidence: 99%